Crisis Resolution: Next Steps - Eichengreen, Barry J.; Kletzer, Kenneth (Cambridge, Mass. National Bureau of Economic Research, 2003)
At the April 2003 meeting of the International Monetary and Financial Committees, it was decided to further encourage the contractual approach to smoothing the process of sovereign debt restructuring by encouraging the more widespread use of collective action clauses (CACs) in international bonds. This decision was shaped partly by Mexico's successful launch of a bond subject to New York law but featuring CACs, and by subsequent issues with similar provisions from other emerging market countries. This paper reviews the developments leading up to that event, its implications, and prospects for the future. It asks whether we can expects to see additional issuance by emerging markets of bonds featuring CACs, whether such a trend would in fact help to make the world a safer financial place, and what additional steps might be taken to further enhance modalities for crisis resolution.
November 2003.
Mode of access: World Wide Web.
Keywords: Bonds -- Developing countries; Debt relief -- Developing countries; Financial crises; Bonds; Debt relief; Financial crises; Developing countries; International Monetary Arrangements and Institutions; International Lending and Debt Problems